2005
DOI: 10.1159/000084843
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Threshold Shift Caused by Acute Cochlear Mitochondrial Dysfunction Is Primarily Mediated by Degeneration of the Lateral Wall of the Cochlea

Abstract: Mitochondrial dysfunction in the cochlea is thought to be an important cause of sensorineural hearing loss. Recently, we have established a novel rat model with acute hearing impairment caused by exposure to the mitochondrial toxin 3-nitropropionic acid (3-NP) to analyze the mechanism of cochlear mitochondrial dysfunction. Both permanent and temporary threshold shifts were observed in this model depending on the amount of 3-NP used to induce hearing impairment. In this study, we demonstrate cochlear morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 106 publications
2
29
0
Order By: Relevance
“…The Na + /K + /Cl − co-transporter expressed by strial marginal cells lies within the~30 cM 95% confidence for Nirep. There are some similarities between the acute pathology we find in BALB and CBA and the effects of metabolic poisons (Hoya et al 2004;Okamoto et al 2005;Yamasoba et al 2006) and locally applied furosemide , suggesting that Nirep encodes the co-transporter, or some factor involved in metabolism.…”
Section: Anatomic Correlates Of Permanent Ep Reductionmentioning
confidence: 67%
“…The Na + /K + /Cl − co-transporter expressed by strial marginal cells lies within the~30 cM 95% confidence for Nirep. There are some similarities between the acute pathology we find in BALB and CBA and the effects of metabolic poisons (Hoya et al 2004;Okamoto et al 2005;Yamasoba et al 2006) and locally applied furosemide , suggesting that Nirep encodes the co-transporter, or some factor involved in metabolism.…”
Section: Anatomic Correlates Of Permanent Ep Reductionmentioning
confidence: 67%
“…Yet this need not promote overt strial pathology. Notably, mitochondrial inhibitors applied in guinea pigs reproduce many of the features of noise injury (Hoya et al 2004;Okamoto et al 2005), while gap junction inhibitors only somewhat reproduce the effects of noise (Spiess et al 2002). In any event, the appearance of the lateral wall does not readily indicate which cells or genes may drive phenotypic differences.…”
Section: Genes and Processes That Establish Or Modulate The Epmentioning
confidence: 97%
“…Mitochondrial degeneration in the SL, as in the SG, plays a crucial role; in a mouse model of DFN3, fibrocytes had fewer mitochondria (Minowa et al 1999), and in mice exposed to a mitochondrial toxin, 3-nitropropionic acid (3-NP) (Okamoto et al 2005), SL pathology was accompanied by hearing loss. Systemic administration of a caspase inhibitor prior to and during 3-NP administration suggested that caspasedependent apoptosis of fibrocytes takes place as a result of mitochondrial damage (Mizutari et al 2008).…”
Section: Introductionmentioning
confidence: 99%